Two new species of phytoseiid mites from southern Africa - Zannou, I.; Moraes, G. de; Hanna, R. (2002)
Two new species of Phytoseiidae (Acari: Mesostigmata) from southern England, Neoseiulus paramarinus and Typhlodromus ulex are described. A redescription is given of Typhlodromus tiliae Oudemans, 1929 based on the examination of the holotype female.